THE ROLE OF WOMEN IN SUSTAINABLE ECOTOURISM MANAGEMENT IN WAKATOBI REGENCY TO ACHIEVE SDGS GOAL 5 ON GENDER EQUALITY. - Marlina Marlina; Abdul Malik; Hasriyanti Hasriyanti; Irwansyah irwansyah (USN Kolaka, 2026)
Women in ecotourism play a key role as capital to achieve sustainable development. This study aims to determine how the role of Bajo Mola women in the development of sustainable ecotourism in Wakatobi district to achieve SDGs Goal 5, namely gender equality. This study uses a qualitative approach, data collection through participatory observation, in-depth interviews, and documentation. Informants in this study were selected by purposive sampling consisting of women, government, community, traditional and religious leaders. Data analysis techniques with data reduction, data presentation, drawing conclusions. The results of the study show that in general there are three roles carried out by women to support the development of sustainable ecotourism, namely: (1) involved in conservation efforts, namely Bajo women are involved as supervisors in management, namely by participating in supporting the utilization of marine potential that prioritizes sustainability. (2) in the role of improving the economy of Bajo women as tour guides, developing seafood-based culinary, and producing handicrafts from marine potential, and active in marketing marine products to local markets and to various regions, for example to Kendari, West Nusa Tenggara and to Java Island. (3) The role of education and teaching in ecotourism is that Bajo women are agents as guardians of local values to each generation and educational agents through tourism activities that are rich in cultural values and environmental preservation. Ecotourism principles such as conservation, community participation, respect for local culture, education, and contribution to the local economy have been implemented by the Bajo Mola community, although they still require ongoing support from various parties. This study confirms that Bajo women have a strategic position in realizing inclusive and sustainable ecotourism. This shows that the role of women in ecotourism is very important to support the achievement of SDGs goal 5, especially target 5.1, namely gender equality in employment and economic benefits.